PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN CONSUMER GOODS SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Abdul Haris Saepudin; Novi Permata Indah (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study aims to obtain empirical evidence of the effect of liquidity ratios, solvency, and profitability on stock prices. The liquidity ratio is measured using the Current Ratio (CR), the solvency ratio is measured using the Debt to Equity Ratio (DER), the profitability ratio is measured using the Return on Equity (ROE). The sampling method is purposive sampling. The sample includes 10 companies in the food and beverage sub-sector on the Indonesia Stock Exchange (IDX) for the period 2016 to 2020. The hypothesis in this study was tested using multiple linear regression analysis model with Eviews12 software. The results of this study prove that simultaneously CR, DER and ROE affect the stock prices of food and beverage sub-sector companies listed on the IDX for the 2016-2020 period. Partially CR and ROE have an effect on stock prices and DER have no effect on stock prices for banking companies listed on the IDX for the 2016-2020 period. Based on the results of the regression analysis, it can be seen that the variables that have a significant influence on stock prices of the food and beverage sub-sector are Current Ratio and Return on Equity variables. That means, the variable in this study becomes a variable that can be used as a reference for investors in determining investment strategies.